Campus Solution: the Case of the Debrecen University Libraries - Virágos, Márta (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
After Word War II, universities in Hungary were split, and their respective faculties became independent institutions. In the 1980s, even before integration became a government priority, negotiations began regarding the reunification of the segregated institutions of higher education in Debrecen. The Debrecen Universities Association (DUA) was founded officially in 1991. On January 2000, the most respectable and complex educational organization in Debrecen came into existence. Fifteen faculties covering a wide range of disciplines and a 35,000-member student body make the University of Debrecen one of the largest universities in Hungary. Since that time, the University and National Library, with an integrated management and organization, has been a central unit of the University.